Konstruksi Media Dalam Memberitakan Politisi Perempuan Yang Terlibat Korupsi (Analisis Framing Kritis Pemberitaan Harian Umum Kompas Terhadap Kasus Korupsi Angelina Sondakh) - Dila Novita (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2016)
This research discusses how Kompas Daily’s reported on the case of Angelina Sondakh’s corruption. This study is aqualitative research with critical framing analysis, adoption of the Radical Feminism theory by Kate Millet. The primary data techniques collected by Kompas news text and the secondary data techniques collected by in-depth interviews. The result of the study found the fact that views of Kompas news on Angelina Sondakh’s corruption case is not solid and comprehensive. It puts Angie just as the actor of corruption, not as the victim of the patriarchal culture that took place in the political parties, the content of the gender bias as many as accentuate the feminine side of a woman